A comparative study of synthetic approaches towards total synthesis of histrionicotoxin: a selective inhibitor of nicotinic acetylcholine receptors. Issue 10 (3rd October 2021) - Shabir, Ghulam; Saeed, Aamer; Ali, Farman
Abstract: The aim of this review is to provide a critical and comparative account of the total synthetic approaches toward histrionicotoxins, alkaloids isolated from skin extracts of Colombian poison arrow frog Dendrobates histrionicus . We have summarized the maneuvers in each paper by graphically detailing the synthesis and associated reaction niceties of only the key intermediates by different researchers. Fascinating structural feature of histrionicotoxins is "8-hydroxy-l-azaspiro[5.5]undecane core" with two side chains at C-2 and C-7 which differ in their length and nature of unsaturation. All synthetic approaches to histrionicotoxins aim at the construction of key intermediate "azaspiro[5.5]undecane ring" and installation of side chains at C-2 and C-7. Graphical abstract: UF0001